2019
DOI: 10.22175/mmb2019.08.0033
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Chicken Thigh Meat by Pulsed Ultraviolet Light

Abstract: Foodborne illness outbreaks associated with chicken can be reduced with effective decontamination interventions. The effectiveness of pulsed ultraviolet (PUV) light for destruction of Salmonella, E. coli, and Campylobacter on the surface of chicken thigh meat was investigated. Chicken thighs were inoculated to 6 to 7 log10 CFU/cm2 before exposure to PUV light for each of the above-mentioned pathogens. Treatment variables included the distance from the quartz window of the PUV light (8 and 13 cm) and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…coli K12 was selected as a nonpathogenic surrogate microorganism to replace Salmonella and Campylobacter. Previous research indicates that E. coli K12 act similar to Salmonella and Campylobacter in different food systems (Keklik et al, 2009;Cassar et al, 2019). Cultures were acquired from the E. coli Reference Center at Pennsylvania State University (University Park, PA).…”
Section: Microorganismmentioning
confidence: 99%
See 2 more Smart Citations
“…coli K12 was selected as a nonpathogenic surrogate microorganism to replace Salmonella and Campylobacter. Previous research indicates that E. coli K12 act similar to Salmonella and Campylobacter in different food systems (Keklik et al, 2009;Cassar et al, 2019). Cultures were acquired from the E. coli Reference Center at Pennsylvania State University (University Park, PA).…”
Section: Microorganismmentioning
confidence: 99%
“…Previous research using a lab benchtop unit demonstrated the antimicrobial effects of PUV light on the surface of raw chicken (Keklik et al, 2009;Cassar et al, 2019). Keklik et al (2009) studied the effect of PUV light for the reduction of Salmonella serovar Typhimurium on the surface of boneless/skinless (B/S) chicken breast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penggunaa sinar ultraviolet pada bahan pangan telah banyak telah banyak dilakukan penelitian, antara lain; penggunaan sinar ultraviolet sebagai bakterisida untuk daging mentah (Stermer,1987), Penggunaan sinar ultraviolet untuk megurangi bakteri patogen dan bakteri pembusuk pada daging ayam filet (Mcleod, 2017), Dekontaminasi daging paha ayam menggunakan pulsed ultraviolet (Cassar, 2019), penggunaan UV untuk sterilisasi makanan sonde (Sulatri,2017). Pada penelitian ini akan dilakukan penerapan sterilisasi metode sinar UVC pada kultur mikroba isolasi dari ikan asap pinekuhe untuk memperkuat hipotesis pada penerapannya secara langsung pada produk ikan asap pinekuhe.…”
Section: Pendahuluanunclassified
“…Recently, several researchers have shown that PUVL treatments are effective in inactivating E. coli on meat surfaces. At 1.27 J cm −2 PUVL, E. coli on lean surface chicken thighs was reduced by 1.22 and 2.02 log 10 CFU cm −2 , whereas PUVL treatment on skin surface thighs resulted in 1.19 and 1.96 log 10 CFU cm −2 reductions with 5 and 45 s treatments, respectively (Cassar et al ., 2019). Treatments with 1.25 to 18.0 J cm −2 PUVL against E. coli resulted in reductions of 0.9 to 3.0 log 10 CFU cm −2 on chicken fillets (McLeod et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%